2021
DOI: 10.1080/14675986.2021.1878112
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes we have to clash’: how preschool teachers in Sweden engage with dilemmas arising from cultural diversity and value differences

Abstract: The research presented in this paper explores how preschool teachers in Sweden negotiate tensions stemming from perceived cultural dilemmas among themselves, the children they work with, and the children´s parents or guardians. The aim in characterising this process of negotiation is to expand knowledge about how to adapt pedagogically to the increasing diversity of the preschool sector in Sweden. The study is based on focus group interviews with preschool teachers who work in schools where nearly 70% of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…They reported not benefiting from the universal language of music, dance, or pictures. Anderstaf et al (2021) stated in their study in a school in Sweden that contains 70% different cultures that teachers encounter similar problems. Still, they also use different cultures as the source and solution of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…They reported not benefiting from the universal language of music, dance, or pictures. Anderstaf et al (2021) stated in their study in a school in Sweden that contains 70% different cultures that teachers encounter similar problems. Still, they also use different cultures as the source and solution of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…In our own research, we have observed that preschool teachers come to similar conclusions about the nature of community in preschool. For example, teachers working in culturally diverse Swedish preschools, when negotiating cultural tensions with parents and guardians, came to see the constitution of community within and beyond preschool walls as situated and contingent (Anderstaf et al, 2021). That is, they came to see each preschool (including individual departments) as places where groups of people routinely interact around shared activities, each contributing knowledge, values, and practices to create diverse idiocultures (Fine, 1979) within and between the departments that made up their preschools.…”
Section: Education and The Sustainable Development Goals: Unesco's Ed...mentioning
confidence: 99%
“…The practitioners try to 'foster' the migrant parents to become preschool parents typical of the host society (Lunneblad 2013(Lunneblad , 2017Sønsthagen 2020). In Sweden, studies also indicate that preschool practitioners are uncertain about confronting value differences and handling diversity, which might be rooted in the desire to avoid conflicts (Anderstaf, Lecusay, and Nilsson 2021).…”
Section: State Of the Artmentioning
confidence: 99%